PENGARUH SIKAP-ATAS-PROFESI, LINGKUNGAN KERJA, DAN KETERAMPILAN TEKNIS TERHADAP KINERJA PAMONG BELAJAR DI SANGGAR KEGIATAN BELAJAR, JAWA BARAT TAHUN 2008 - Erman Syamsuddin (JIV-Jurnal Ilmiah Visi, 2009)
The aims of this research were to discover: (1) the effect of technical skill on tutor’s performance, (2) the effect of attitude towards profession on tutor’s performance, (3) the effect of work environment on tutor’s performance, (4) the effect of attitude toward profession on tutor’s technical skill, (5) the effect of work environment on tutor’s technical skill, (6) the indirect effect of attitude towards profession on tutor’s performance through tutor’s technical skill, and (7) the indirect effect of work environment on tutor’s performance through tutor’s technical skill. Using causal survey with path analysis, the research was conducted at 7 Sanggar Kegiatan Belajar in West Java from July 2007 to January 2008. Samples were determined by multistage random sampling technique over 125 respondents. The steps of the research were as follow: conducting pre-survey and tryout for instrument, collecting data, analyzing data, and writing dissertation. The research found out five significant direct effects, namely: (1) technical skill on tutor’s performance, (2) attitude towards profession on tutor’s performance, (3) work environment on tutor’s performance, (4) attitude towards profession on tutor’s technical skill, and (5) work environment on tutor’s technical skill. The study also showed two indirect effects: attitude towards profession on tutor’s performance through tutor’s technical skill, and work environment on tutor’s performance through tutor’s technical skill. The research concludes that tutor’s performance can be improved through attitude towards profession, work environment and technical skill.